A factor analysis of residents' performance in municipal solid waste source-separated collection: A case study of pilot cities in China. (3rd August 2019) - Zou, Can; Tai, Jun; Wang, Yu; Sun, Fengyun; Che, Yue
ABSTRACT: To explore the potential effectiveness of a localized waste recycling system in Chinese cities, several rounds of a municipal solid waste source-separated collection (MSWSC) program were implemented throughout China from 2000 to 2017. In our study, to evaluate the achievements of the MSWSC program, a structured questionnaire survey and face-to-face interviews were conducted in eight representative cities from the MSWSC pilot cities. Influencing factors were examined via a Hierarchical Linear Model (HLM) on both the individual level and the city level. The differences in MSWSC performance among the eight research cities were investigated through a comparative analysis. The results suggested that gender, age, knowledge of MSWSC, satisfaction with sanitation and satisfaction with publicity had significant impacts on MSWSC, and we further found that the city-level factors influenced the relationship between MSWSC performance and the individual-level variables. Differences among the eight research sites indicated that Nanjing and Hangzhou exhibited relatively high achievements in the implementation of MSWSC program, while Yichun and Guiyang showed poor performance. The experiences of these advanced pilot cities suggest that specific containers for designated waste types, widespread public education, and sufficient MSWSC incentives must be provided and publicized to promote municipal solid waste recycling behaviors. Given the unique status of municipal solid waste management in China and its regional heterogeneity, the MSWSC system should be further discussed with regard to local conditions in a wider range of city settings. Implications : This study attempts to discuss the factors affecting performance on municipal solid waste source-separated collection (MSWSC) by considering the nested data of two levels of individual and city from a structured questionnaire survey. Therefore, a Hierarchical Linear Model is established which can analyze the intra-group and inter-group effects of two-level variables. The proposed method can be expanded to other cities to determine the main factors affecting MSWSC or to evaluate the residents' performance on MSWSC.